2018
DOI: 10.1590/0001-3765201820170766
|View full text |Cite
|
Sign up to set email alerts
|

The exotic jumping snail Ovachlamys fulgens (Gude, 1900) (Gastropoda: Helicarionidae) in urban areas of the Upper-Paraná Atlantic Forest

Abstract: The exotic land gastropod Ovachlamys fulgens (Gude, 1900), aka the jumping snail, was registered in Eldorado city, Misiones province, constituting the first documented record of that species in Argentina-and for all of South America as well. Identities of the individuals were confirmed through morphological examination, and by a DNA sequencing of the cytochrome oxidase subunit I gene. DNA sequences for the mitochondrial 16S-rRNA and the nuclear 18S-rRNA genes were also obtained from the morphologically-confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…In Paraná, it was collected in a hotel garden, in Vila Olimpia neighborhood. This last report is the closest to Eldorado, in Missiones, Argentina, where the species is also recorded (Beltramino et al 2018).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In Paraná, it was collected in a hotel garden, in Vila Olimpia neighborhood. This last report is the closest to Eldorado, in Missiones, Argentina, where the species is also recorded (Beltramino et al 2018).…”
Section: Discussionmentioning
confidence: 72%
“…Teixeira et al (2017) found specimens in leaf litter of a very disturbed patch of Atlantic Forest and in a orchid nursery, occuring in the same enviroment of native species in São Paulo. Beltramino et al (2018) registered the species in an urban environment, in Eldorado, Argentina, located in a mosaic of native forest, plantations, agriculture and pastures. Besides, Salles et al (2018) collected the species within the Atlantic forest area, within Parnaso Park, mainly on the margins of trails.…”
Section: Discussionmentioning
confidence: 99%
“…The soft parts were dissected using a Labomed Luxeo 4D stereomicroscope for the study of the reproductive system. Genomic DNA was isolated from a portion of pedal muscle of the same morpho-anatomical analyzed specimens by means of a cetyltrimethylammonium bromide protocol (Beltramino et al 2018). Partial sequences of the 16S-rRNA mitochondrial marker were amplified by polymerase chain reaction (PCR) using the primers 16SF-104 and 16SR-472 (Ramirez and Ramírez 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Total DNA was extracted from three mm 3 samples of foot muscle of ethanol-preserved specimens by means of a cetyltrimethylammonium bromide protocol (Beltramino et al, 2018). We selected 16 samples belonging to Clessinia and Spixia species and the outgroup species Plagiodontes daedaleus .…”
Section: Methodsmentioning
confidence: 99%